Presence of Violeta Parra in the Construction of the Popular Imaginary of the Chilean Road to Socialism. la Peña de Los Parra and la Carpa de la Reina: The Reconstruction of a Testimonial Memory [Presencia de Violeta Parra en la Construcción del Imaginario Popular de la Vía Chilena Al Socialismo. la Peña de Los Parra y la Carpa de la Reina: La Reconstrucción de Una Memoria Testimonial] - Montealegre-Iturra, J; Chavarria-Contreras, R (Universitat de Valencia, Faculty of Philology, Translation and Communication, 2021)
Violeta Parra s work, as well as her artistic/folkloric legacy, was instrumental to the emergence of an insurgent popular culture which left its mark on the Allende presidency and post-dictatorial memorializations. The Peña de los Parra and the Carpa de la Reina were cultural artifacts born out of the Parra family s artistic practices. Their reconstruction by means of testimonial memories brings back the complex socio-cultural context in which they were immersed. Both artifacts contain memories which connote forms of artistic involvement that announce symbolic associations with the political process unleashed by the Unidad Popular, subsequently crushed by the 1973 military coup. This article attempts an "ex post" reading of both experiences, resorting to the testimonial reconstruction of those memories, and applying notions born out of cultural and memorial studies. The chronology thus pieced together enables a recreation of the Peña s and the Carpa s accomplishments that emerges as a useful inquiry into the significant partaking of the distinguished Parra family, led by Violeta Parra, in major historical processes. © 2021 Universitat de Valencia, Faculty of Philology, Translation and Communication. All rights reserved.